2021
DOI: 10.1080/17434440.2021.1969913
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive vagus nerve stimulation in Parkinson’s disease: current status and future prospects

Abstract: Introduction: Parkinson's disease (PD) is a common progressive neurodegenerative disorder with multifactorial etiology. While dopaminergic medication is the standard therapy in PD, it provides limited symptomatic treatment and non-pharmacological interventions are currently being trialed. Areas covered: Recent pathophysiological theories of Parkinson's suggest that aggregated α-synuclein form in the gut and spread to nuclei in the brainstem via autonomic connections. In this paper, we review the novel hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 167 publications
(248 reference statements)
0
19
0
Order By: Relevance
“…It establishes a crucial connection between the brain and the gastrointestinal tract and sends information about the state of the inner organs to the brain, which aids in homeostasis of bodily functions. Vagus nerve stimulation is a promising supportive treatment for refractory depression, posttraumatic stress disorder, and inflammatory bowel disease, inhibits cytokine production, and positively effects beneficial monoaminergic brain signaling in psychiatric conditions, such as mood and anxiety [ 61 , 62 , 63 ], and also for the treatment of traumatically injured brain tissues [ 64 , 65 , 66 , 67 , 68 , 69 ]. Gut bacteria have beneficial effects on mood and anxiety through the bioactive factors they produce, which are transported by the vagus nerve to the brain.…”
Section: Therapeutic Vagus Nerve Stimulationmentioning
confidence: 99%
“…It establishes a crucial connection between the brain and the gastrointestinal tract and sends information about the state of the inner organs to the brain, which aids in homeostasis of bodily functions. Vagus nerve stimulation is a promising supportive treatment for refractory depression, posttraumatic stress disorder, and inflammatory bowel disease, inhibits cytokine production, and positively effects beneficial monoaminergic brain signaling in psychiatric conditions, such as mood and anxiety [ 61 , 62 , 63 ], and also for the treatment of traumatically injured brain tissues [ 64 , 65 , 66 , 67 , 68 , 69 ]. Gut bacteria have beneficial effects on mood and anxiety through the bioactive factors they produce, which are transported by the vagus nerve to the brain.…”
Section: Therapeutic Vagus Nerve Stimulationmentioning
confidence: 99%
“…This association has been previously found in both the quantity (i.e., habitual physical activity) and quality of gait (e.g., spatio-temporal characteristics) in PD. For example, Loprinzi, et al [ 27 ] reported a favourable association between greater moderate-vigorous physical activity and global cognitive function in PD [ 28 ], while significant evidence has been gathered towards the role of cognition in gait quality, as demonstrated by dual-task gait impairments [ 29 , 30 , 31 , 32 ] and the impact of treatments targeting cholinergic pathways [ 33 ]. Therapeutics for cognitive and motor symptoms may aid the maintenance of HPA; for example, deep brain stimulation treatment for six months led to significant increases in walking bout lengths and variability in PwP [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, any invasive intervention must be carefully weighed in LBD, and specific trials in patients with dementia will be needed to facilitate a balanced judgement on the risks and benefits of HGNS in LBD and other dementias. Transcranial magnetic stimulation (TMS) may have potential for the treatment of multiple symptom domains in LBD, including sleep disorders 195,196 . Studies have reported beneficial effects for TMS on RLS 197 and EDS (in a recent small RCT in PDD), 198 while a study 199 showed that TMS can also increase respiratory airflow in OSA, by stimulating submental muscles without inducing wakefulness, suggesting that TMS could be a viable non‐invasive strategy for treating OSA in the future.…”
Section: Novel and Emerging Therapeutics For Sleep Disorders In Lbdmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) may have potential for the treatment of multiple symptom domains in LBD, including sleep disorders. 195,196 Studies have reported beneficial effects for TMS on RLS 197 and EDS (in a recent small RCT in PDD), 198 while a study 199 showed that TMS can also increase respiratory airflow in OSA, by stimulating submental muscles without inducing wakefulness, suggesting that TMS could be a viable non-invasive strategy for treating OSA in the future. Vagal nerve stimulation (VNS) has been shown to improve EDS in treatment-resistant epilepsy.…”
Section: Neuro-modulation Presents Another Alternative Tomentioning
confidence: 99%